Penelitian Umkm: Analisis Keunggulan Dan Strategi Pemasaran Pada 'Seblak Teh Windy’ - Rakhman, Arif; Maula, Kholida Atiyatul; Kristina, Kristina; Natalia, Ovia; Rachmasari, Ananda Putri; Puspariani, Wini; Ayumi, Shafira Mega; Febriana, Ellyza; Kowiyah, Elita (Peneliti.net, 2024)
This report documents the results of an interview with the owner of the micro, small, and medium-sized enterprise (MSME)